Molecular diversity of Sarcocystis spp. in opossums (Didelphis spp.) from Southeastern and Midwestern Brazil - De Santi, Mariele [UNESP]; André, Marcos Rogério [UNESP]; Werther, Karin [UNESP]; Gonçalves, Luiz Ricardo; Soares, Rodrigo Martins; Herrera, Heitor Miraglia; Santos, Filipe Martins; Sano, Nayara Yoshie; de Assis, William Oliveira; Rucco, Andreza Castro; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2023)
South American opossums (Didelphis spp.) are definitive hosts of Sarcocystis neurona, Sarcocystis speeri, Sarcocystis lindsayi and Sarcocystis falcatula. In Brazil, diverse studies have demonstrated a high frequency of Sarcocystis falcatula-like in sporocysts derived from opossums, and high genetic diversity has been observed in surface antigen-encoding genes (SAGs). In this study, genetic diversity of Sarcocystis spp. derived from Didelphis albiventris and Didelphis aurita from the cities of Campo Grande and São Paulo, was accessed by sequencing SAG2, SAG3, SAG4, the first internal transcribed spacer (ITS-1) and cytochrome c oxidase subunit I (cox1). Molecular identification was performed for 16 DNA samples obtained from sporocyst or culture-derived merozoites. The ITS-1, cox1, and SAG3 fragments were cloned, whereas SAG2 and SAG4 were sequenced directly from PCR products. Four alleles variants were found for SAG2, 13 for SAG3 and seven for SAG4, from which four, 13 and four, respectively, were novel. Twentyseven allele variants were found for ITS-1, all phylogenetically related to S. falcatula-like previously described in Brazil. Sarcocystis sp. phylogenetically related to Sarcocystis rileyi was evidenced by cox1 in three opossums. Further studies are needed to clarify the role of Didelphis spp. as definitive hosts of Sarcocystis spp. other than that previous described.
Diversidade molecular de Sarcocystis spp. em gambás (Didelphis spp.) do Sudeste e Centro-oeste do Brasil
Keywords: cox1; ITS-1; molecular characterization; opossums; SAGs; Sarcocystis spp